Analysis of The Success of Labor Intensive Program in Building Village Infrastructure - Feri, Feri; Putra, Muhammad Amril Pratama; Mone, Ansyari; Hartaman, Nursaleh (Universitas Muhammadiyah Makassar, 2024)
This study aims to determine the effectiveness of the labor-intensive program in infrastructure development in Ulubalang Village, Bone Regency. The main objective of this study was to evaluate the positive impact of the program on the progress of village infrastructure. The research method involved field surveys, interviews, as well as statistical data analysis to measure the success rate of labor-intensive program implementation. The results showed that the program significantly improved economic access and increased community access to infrastructure such as roads and bridges. This is seen from the labor-intensive effectiveness theory used to describe and explain labor-intensive in village development, which is viewed from the source approach, process approach, and target approach. In addition, this study found that the labor-intensive program also had a positive impact on improving community skills and participation in village development. The program not only improves physical infrastructure, but also empowers local communities through employment and training opportunities. The success of the labor-intensive program in improving village infrastructure is also reflected in the high level of community satisfaction with the development results achieved.